Hepatitis B Virus-Encoded X Protein Downregulates EGFR Expression via Inducing MicroRNA-7 in Hepatocellular Carcinoma Cells. (11th June 2013) - Chen, Yun-Ju; Chien, Pei-Hsuan; Chen, Wen-Shu; Chien, Yu-Fong; Hsu, Ya-Ying; Wang, Li-Yun; Chen, Jhen-Yu; Lin, Chih-Wen; Huang, Tzung-Chi; Yu, Yung-Luen; Huang, Wei-Chien
Abstract : Hepatitis B virus (HBV) infection accounts for over a half of cases of hepatocellular carcinoma (HCC), the most frequent malignant tumor of the liver. HBV-encoded X (HBx) plays critical roles in HBV-associated hepatocarcinogenesis. However, it is unclear whether and how HBx regulates the expression of epidermal growth factor receptor (EGFR), an important gene for cell growth. Therefore, the study aimed to investigate the association between HBx and EGFR expression. In this study, we found that HBx upregulates miR-7 expression to target 3′UTR of EGFR mRNA, which in turn results in the reduction of EGFR protein expression in HCC cells. HBx-mediated EGFR suppression renders HCC cells a slow-growth behavior. Deprivation of HBx or miR-7 expression or restoration of EGFR expression can increase the growth rate of HCC cells. Our data showed the miR-7-dependent EGFR suppression by HBx, supporting an inhibitory role of HBx in the cell growth of HCC. These findings not only identify miR-7 as a novel regulatory target of HBx, but also suggest HBx-miR-7-EGFR as a critical signaling in controlling the growth rate of HCC cells.